2007
DOI: 10.1111/j.1538-7836.2007.02474.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune tolerance therapy for factor VIII inhibitors: moving from empiricism to an evidence-based approach

Abstract: To cite this article: DiMichele D. Immune tolerance therapy for factor VIII inhibitors: moving from empiricism to an evidence-based approach. Summary. Currently, the only proven strategy for achieving antigen-specific tolerance to factor VIII (FVIII) is immune tolerance induction (ITI) therapy. This paper discusses our current knowledge of the host and treatment factors, as well as supportive care initiatives, known or suspected to influence the outcome of ITI in the treatment of inhibitors arising in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 61 publications
(83 reference statements)
0
35
0
Order By: Relevance
“…Systemic complications associated with inhibitory antibodies to FIX include anaphylactic reaction and nephrotic syndrome. 30,31 Importantly, Wiley showed no evidence of abnormal kidney function or urinary protein loss (data not shown). To confirm the eradication of inhibitory antibody to cFIX and immune tolerance induction, Wiley was challenged with 0.5 mg cFIX-WT protein concentrate 2.3 years after vector injection.…”
Section: Canine Studiesmentioning
confidence: 99%
“…Systemic complications associated with inhibitory antibodies to FIX include anaphylactic reaction and nephrotic syndrome. 30,31 Importantly, Wiley showed no evidence of abnormal kidney function or urinary protein loss (data not shown). To confirm the eradication of inhibitory antibody to cFIX and immune tolerance induction, Wiley was challenged with 0.5 mg cFIX-WT protein concentrate 2.3 years after vector injection.…”
Section: Canine Studiesmentioning
confidence: 99%
“…This has led to an increasing interest in developing new protocols for the induction of tolerance to therapeutically administered clotting factors. 3 Recent clinical trials have explored the putative higher tolerogenicity of factor VIII (FVIII) coupled with von Willebrand factor or B-cell depletion with the anti-CD20 monoclonal antibody (mAb) rituximab. 4,5 The outcome of those trials has shown, at the most, a modest improvement in ITI efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been related to the development of inhibitors, the most strongly associated is a type of genetic mutation of FVIII, as well as the type of Human Leucocitary Antigen (HLA) and the polymorphisms in the genes codified for cytokines (African or Hispanic background) of each individual [34], as well as the type of replacement therapy used and the age of starting up. In a study by Santagostino and Mancuso [20], 25 out of 108 children with haemophilia received prophylaxis and had a lower inhibitor risk than those treated on-demand (adjusted OR 0.2; CI: 0.06-0.9), suggesting a protective effect of prophylaxis from inhibitor development.…”
Section: Summary Of Findings On Treatmentmentioning
confidence: 99%